Aneka Kerepek Anin / Nur Anissa Mohd Asri and Nur Ain Ismail - Mohd Asri, Nur Anissa; Ismail, Nur Ain (2022)
Aneka Kerepek Anin is a new form of business in the food and beverage industry which just recently started their business on 1 st June 2022. The business offers an addicting chip with various options and flavor. This business is a partnership-based business that consists of two partners which are Nur Anissa and Nur Ain which they both are childhood friends. This business is registered in SSM and E-Commerce as a legit business. Aneka Kerepek Anin are available through offline and online platforms. Customers can buy this product on social media, specifically Facebook with the name, @anekakerepekanin. This business does cover three different locations which are UiTM Puncak Alam, Selangor, Nilai, Negeri Sembilan: and Putrajaya, Federal territory of Putrajaya. Customers also can choose options for the delivery such as through postage or cash on delivery which is easier and more direct as the buyer and the seller will meet each other faceto-face. This business is co-owned by Nur Anissa and Nur Ain as the business partner and there are two other staff who work for them. The mission for Aneka Kerepek Anin is to run a profitable food store and business in Malaysia while simultaneously looking ahead to better opportunities. Whereas the vision of the company is to offer the finest food (chips) that is delicious, homemade, and will make consumers of all ages happy. We have decided to register as an E-commerce platform as we have discovered how convenient to use it and how profitable it can be as the Covid-19 spreaders happen. We realize that many people spend most of their time using mobile phones and online platforms. That is how we decided to register e-commerce and create our Facebook page to promote our business and products. As our strategy to attract customers on Facebook, we decided to use the hard-sell and softsell method which will help us to provide information regarding our product, such as the benefits and price. In this report, we also gather all of our materials such as teaser photos that we post to promote and attract potential customers. Other than that, we also decided to post graphics of our product to introduce our product to the world. Our product is loved by many and we gain profits by selling chips.